2015
DOI: 10.1098/rspa.2015.0471
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic phenomena in pressurized thin films

Abstract: An asymptotic study of the wrinkling of a pressurized circular thin film is performed. The corresponding boundary-value problem is described by two nondimensional parameters; a background tension μ and the applied loading P. Previous numerical studies of the same configuration have shown that P tends to be large, and this fact is exploited here in the derivation of asymptotic descriptions of the elastic bifurcation phenomena. Two limiting cases are considered; in the first, the background tension is modest, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…In keeping with the related work reported in [8] we have assumed 0 < ε 1, so that λ = O(1) and m = O(ε −3/2 ). As explained in that reference, for a low or moderate degree of initial stretching it follows that ε is no longer very small and, in fact, the limits ε 1 or ε = O(1) might become relevant (note that in the notation of [12] this corresponds to 0 < µ 1 and µ = O(1), respectively). In that case the roots of the characteristic equation (3.3) are rather different from what we found in §3, and it can be shown that the asymptotic reduction of §4 leads to contributions from both equations in (2.14), which can then be combined into a parabolic-cylinder type second-order differential equation.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…In keeping with the related work reported in [8] we have assumed 0 < ε 1, so that λ = O(1) and m = O(ε −3/2 ). As explained in that reference, for a low or moderate degree of initial stretching it follows that ε is no longer very small and, in fact, the limits ε 1 or ε = O(1) might become relevant (note that in the notation of [12] this corresponds to 0 < µ 1 and µ = O(1), respectively). In that case the roots of the characteristic equation (3.3) are rather different from what we found in §3, and it can be shown that the asymptotic reduction of §4 leads to contributions from both equations in (2.14), which can then be combined into a parabolic-cylinder type second-order differential equation.…”
Section: Discussionmentioning
confidence: 98%
“…However, we also draw attention to a number of "clues" that could have anticipated the main findings reported in this work. For instance, the more orthodox boundary-layer approach pursued in [9] and [12], which dealt with similar situations involving a vertical point-load and a uniform transverse pressure, respectively, revealed that the FvK bifurcation system asymptotically decoupled for µ 1, and its behaviour was driven by a hierarchy of second-order ordinary differential equation originating in our operator L 1 -see (2.15a). Furthermore, we note that the wrinkling scenario investigated by Coman & Haughton in [15] corresponds to letting L 2 ≡ 0 and setting the multiplicative factor λ to unity in (2.14); the effect of these changes leaves the two bifurcation equations trivially decoupled.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations